Giving Ovaprim Hormone Against Fertilization On Red Tilapia (Oreochromis niloticus) - M. Abjan Fabanjo; Nursanti Abdullah; Eko S Wibowo (Agrikan: Jurnal Agribisnis Perikanan, 2021)
Tilapia is one type of freshwater fish that is very popular with people North Maluku community, and has potential economic value to be developed in North Maluku.The production target for consumption needs is still very far from the target requirement. This research was conducted to evaluate the performance of the hormone ovaprim, fecundity, fertilization rate, hatching rate in tilapia.This study was designed using a completely randomized design (CRD). The results showed that the highest degree of healing was found in treatment C at a dose of 0.6 ml/gr bt (85.19%) then treatment B at a dose of 0.4 ml/gr bt (82.78%) A dose 0.2 ml/grm bt of (77%), and dose D (control) did not occur spawning.From the analysis of variance data showed that treatment C at a dose of 0.6 ml/grm bt gave a very significant effect on the percentage of fertilization of tilapia eggs on the value (F count = 117 > F table 0.01 = 7.59